Contrasting Estuarine Processing of Dissolved Organic Matter Derived From Natural and Human‐Impacted Landscapes. Issue 10 (28th September 2021) - García‐Martín, E. Elena; Sanders, Richard; Evans, Chris D.; Kitidis, Vassilis; Lapworth, Dan J.; Rees, Andrew P.; Spears, Bryan M.; Tye, Andy; Williamson, Jennifer L.; Balfour, Chris; Best, Mike; Bowes, Michael; et al.
Abstract: The flux of terrigenous organic carbon through estuaries is an important and changing, yet poorly understood, component of the global carbon cycle. Using dissolved organic carbon (DOC) and fluorescence data from 13 British estuaries draining catchments with highly variable land uses, we show that land use strongly influences the fate of DOC across the land ocean transition via its influence on the composition and lability of the constituent dissolved organic matter (DOM). In estuaries draining peatland‐dominated catchments, DOC was highly correlated with biologically refractory "humic‐like" terrigenous material which tended to be conservatively transported along the salinity gradient. In contrast, there was a weaker correlation between DOC and DOM components within estuaries draining catchments with a high degree of human impact, that is, relatively larger percentage of arable and (sub)urban land uses. These arable and (sub)urban estuaries contain a high fraction of bioavailable "protein‐like" material that behaved nonconservatively, with both DOC removals and additions occurring. In general, estuaries draining catchments with a high percentage of peatland (≥18%) have higher area‐specific estuarine exports of DOC (>13 g C m −2  yr −1 ) compared to those estuaries draining catchments with a high percentage (≥46%) of arable and (sub)urban land uses (<2.1 g C m −2  yr −1 ). Our data indicate that these arable and (sub)urban estuaries tend to export, on average, ∼50% more DOC to coastal areas than they receive from rivers due to net anthropogenic derived organic matter inputs within the estuary. Key Points: Dissolved organic carbon (DOC) mixing dynamics were mainly influenced by the DOM fluorescence components associated with land use types Catchments with a high percentage of arable and (sub)urban land uses tend to export more DOC to coastal areas than they receive from rivers Catchments with a high percentage of peatland have >5‐fold greater area‐specific export of DOC to coastal waters